Local analysis of hybrid systems on polyhedral sets with state-dependent switching - Leth, John; Wisniewski, Rafael (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with stability analysis of hybrid systems. Various stability concepts related to hybrid systems are introduced. The paper advocates a local analysis. It involves the equivalence relation generated by reset maps of a hybrid system. To establish a tangible method for stability analysis, we introduce the notion of a chart, which locally reduces the complexity of the hybrid system.
Keywords: stability; switched systems; hybrid systems; differential inclusions